PENGARUH WISHTLEBLOWING SYSTEM, PENCEGAHAN FRAUD, DAN PERILAKU ETIS TERHADAP LOYALITAS KARYAWAN - Amru Sukmajati; Mar’ah Sholikhah (ITB AAS INDONESIA, 2022)
This study was conducted to determine the effect of the Whistleblowing System, fraud prevention, and ethical behavior on the loyalty of employees of the Limited Liability Company (PT) Bank Perkreditan Rakyat BKK Karangmalang (Perseroda), Sragen Regency. This study uses a quantitative approach. The data source used is primary data obtained using a questionnaire given to employees of the Limited Liability Company (PT) Bank Perkreditan Rakyat BKK Karangmalang (Perseroda), Sragen Regency. The sampling technique in this study was purposive sampling. The scale used in this study is a scale from 1-5. The number of samples taken was 60. This study used multiple linear regression analysis techniques. The results show that the Whistleblowing System has a significant effect on employee loyalty, fraud prevention has a significant effect on employee loyalty, ethical behavior has a significant effect on employee loyalty and the Whistleblowing System, fraud prevention, and ethical behavior simultaneously have a significant effect on employee loyalty.